Recent advances in engineering of tooth and tooth structures using postnatal dental cells - Masaki J. Honda; Shuhei Tsuchiya; Yoshinori Shinohara; Yuka Shinmura; Yoshinori Sumita (Elsevier, 2010)
Since cells isolated from the developing tooth possess an enormous regenerative potential, it has been proposed that they could be applied to the in vivo regeneration of teeth in dental practice. The generation of the entire tooth structure depends upon the developmental stage of tooth when the cells are harvested. This review focuses on the performance of postnatal and adult dental cells that have been used for generating teeth. Their ability to contribute to tooth development was assessed in the omentum or in the tooth socket. Adult dental cells were limited in their potential owing to various parameters. From these results described, new approaches for regenerated teeth are proposed in this review. One strategy to replace teeth is tooth root engineering using tissue from postnatal teeth. Since the enamel organ epithelium disappears after tooth maturation, the epithelial rest cells of Malassez were evaluated to determine their capacity to generate enamel. From these results, it is suggested that erupted mature teeth have cell sources with the capacity to produce tooth root. The development of biological approaches for tooth root regeneration using postnatal dental cells is promising and remains one of the greatest challenges in the dental field in the years to come.